Investigation on Electrochemical Performance of New Flexible Nanocomposite Poly(Vinylidene Fluoride-co-Hexafluoropropylene) Polymer Electrolytes - G. Vijayakumar; A. Maruthadurai; R. Paramasivam; V. Tamilavan (International Journal of Polymer Science)
This research paper as an article investigates electrochemical performance of poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-co-HFP) flexible nanocomposite polymer electrolytes which have been prepared successfully with incorporation of zinc oxide (ZnO) nanofiller. First, nanofillers are incorporated in a polymer matrix to form the flexible nanocomposite PVdF-co-HFP polymer membranes (PI-CMPM), and it is obtained by phase inversion technique. Contact angles of PI-CMPM have achieved a maximum of 136°. After this procedure, it has been activated by using a 1.0 M LiClO4 containing of DMC/EC (1 : 1 v/v ratio) electrolyte solution to get flexible nanocomposite polymer electrolytes (PI-CMPE). The optimized PI-CMPM has increased the electrolyte uptake by 150%. It reaches the maximum ionic conductivity value of 2.47×10−3 S cm−1 at room temperature. Optimized PI-CMPE achieved a maximum transference number of 0.61, which may be further evidence for the ability to fabricate high-performance lithium ion polymer batteries.